Class Condition and Educational Performance in Brazil - Bernardo Mattes Caprara (Educação & Realidade, 2021)
This paper analyzes the effects of social class on the educational performance of young Brazilians students. Our theoretical approach in this study is based on Pierre Bourdieu’s concept of social class. We opted for a quantitative methodology using the database of the Basic Education Evaluation System (Saeb) tests carried out in 2013. We used descriptive statistics, correspondence analysis and multiple linear regression. Empirical results showed the persistence of the effects of social class on academic performance, although these results coexist with the impacts of variables related to schooling, individual life story and pedagogical aspects.